Comparison between gas insufflation and gasless techniques for endoscopic transaxillary thyroidectomy - Lin, Li; Chen, Shuxun; Lu, Yizhuo (Frontiers in Endocrinology, 2024)
Objective: This study aimed to compare clinical outcomes and prognosis of endoscopic thyroidectomy via axillary approach using insufflation and gasless methods. Methods: Retrospective analysis included patients undergoing endoscopic thyroidectomy at our institution from June 2022 to October 2023. Patients were categorized into insufflation and gasless groups. Analysis compared surgical time, blood loss, drainage volume, tube removal time, hospital stay, complications, pain score, and incision satisfaction. Results: 73 patients (48 insufflation, 25 gasless) were analyzed. Insufflation technique showed significantly superior outcomes: shorter surgery duration, reduced drainage volume, earlier tube removal, shorter hospital stay, and higher incision satisfaction (all P < 0.05). Postoperative pain (VAS) was lower in insufflation group on first day, but no significant difference on seventh day. No significant differences in blood loss or complications were observed.Insufflation technique offers advantages over gasless method including shorter operation time, reduced drainage, earlier tube removal, and shorter hospital stays, with comparable outcomes in pain and incision satisfaction.